Working Memory-Theory, Deficits, Diagnosis, and Vision Therapy. - Groffman, Sidney (Optometry & Visual Performance, 2014)
Working memory (WM) is one of the most significant psychological ideas developed in the last forty years. WM is the cognitive function responsible for storing information, manipulating it, and using it in thinking. WM is a multidimensional system comprising three separable yet interactive domains. They are an executive domain and verbal and visual domains. Working memory affects many perceptuo-cognitive activities, and WM deficits can create a variety of problems, many of which fall under the domain of developmental optometry. Research has repeatedly affirmed the hypothesis that WM underlies individual differences in learning ability. The disabilities affected by WM range from ADHD to learning disabilities to traumatic brain injury. Fluid intelligence and working memory have generated much interest and a significant amount of literature. Many studies show that WM training increases fluid intelligence, but others do not agree. A number of WM tests have been produced over the years. A battery of tests should be utilized by practitioners to ensure all aspects of WM. A variety of therapeutic procedures have been developed mostly by psychologists and some educators for improving WM deficits. Techniques that have achieved the best results involve implicit computerized therapy. To determine whether a WM test or therapy technique is truly WM, it must meet one or more of the following requirements: 1. Is any manipulation or transformation of the information required? 2. Is any concurrent or intervening processing required? 3. Are both storage and processing required? 4. Does the task involve the concurrent retention of both visuospatial and verbal information or the recoding of one modality to another? While most developmental optometrists use perceptuo-cognitive tests and therapy materials, some of which touch on WM, many optometrists are not conversant enough with the concepts of WM and how it can benefit our opto metric vision therapy patients.